Genome sequence of an uncharted halophilic bacterium Robertkochia marina with deciphering its phosphate-solubilizing ability - Lam, Ming Quan (Braz J Microbiol, 2020)
The wide use of whole-genome sequencing approach in the modern genomic era has opened a great opportunity to reveal the prospective applications of halophilic bacteria. Robertkochia marina CC-AMO-30D(T) is one of the halophilic bacteria that was previously taxonomically identified without any inspection on its biotechnological potential from a genomic aspect. In this study, we present the whole-genome sequence of R. marina and demonstrated the ability of this bacterium in solubilizing phosphate by producing phosphatase. The genome of R. marina has 3.57 Mbp and contains 3107 predicted genes, from which 3044 are protein coding, 52 are non-coding RNAs, and 11 are pseudogenes. Several phosphatases such as alkaline phosphatases and pyrophosphatases were mined from the genome. Further genomic study (phylogenetics, sequence analysis, and functional mechanism) and experimental data suggested that the alkaline phosphatase produced by R. marina could potentially be utilized in promoting plant growth, particularly for plants on saline-based agricultural land. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s42770-020-00401-2.